Paxillin Enables Attachment-independent Tyrosine Phosphorylation of Focal Adhesion Kinase and Transformation by RAS - Wade, Ramon (American Society for Biochemistry and Molecular Biology, 2011)
Paxillin and HIC5 are closely related adapter proteins that regulate cell migration and are tyrosine-phosphorylated by focal adhesion kinase (FAK). Paxillin, HIC5, and FAK tyrosine phosphorylation increase upon cell attachment and decrease upon detachment from extracellular matrix. Unexpectedly, we found that although FAK tyrosine phosphorylation in attached cells did not require paxillin, in detached fibroblasts there was remaining FAK tyrosine phosphorylation that required expression of paxillin and was not supported by HIC5. The support of attachment-independent FAK tyrosine phosphorylation required the paxillin LIM domains and suggested that paxillin might facilitate oncogenic transformation. Paxillin but not HIC5 augmented anchorage-independent cell proliferation induced by RAS. Both anchorage-independent FAK tyrosine phosphorylation and RAS-induced colony formation required multiple docking sites on paxillin, including LD4 (docking sites for FAK-Src and GIT1/2-PIX-NCK-PAK complex), LD5, and all four carboxyl-terminal LIM domains (that bind tubulin and PTP-PEST). Analysis using paxillin mutants dissociated domains of paxillin that are required for regulation of cell migration from domains that are required for anchorage-independent cell proliferation and demonstrated essential functions of the paxillin LIM domains that are not found in HIC5 LIM domains. These results highlight the role of paxillin in facilitating attachment-independent signal transduction implicated in cancer.